Accounting information systems - Gelinas, Ulric J.; Dull, Richard B. (South-Western/ Cengage Learning, 2010)
Helps you develop a solid foundation in enterprise risk management as it relates to business processes and their information systems. This book covers enterprise systems, e-Business systems, and controls for maintaining those systems